Certain properties of nanohydroxyapatite obtained from Lates calcarifer fish bone - Hy, Le Ho Khanh; Ha, Dao Viet; Ky, Pham Xuan; Anh, Nguyen Phuong; Vy, Phan Bao; Thiet, Doan Thi (Vietnam Journal of Marine Science and Technology, 2021)
Fish bone by-products are considered as abundant source of hydroxyapatite (HAp). The preparation of HAp from fish bones not only contributes to improving the value of by-products but also minimizes negative impacts on the environment. In this study, nanohydroxyapatite was successfully obtained from Lates calcarifer fish bone purchased from seafood export company in Khanh Hoa province. Fish bones were under alkali treatment and then heated at 600oC within different time intervals of 1, 2 and 4 hours. Analysis of XRD and SEM showed that the calcium formed was completely single-phase and possessed an average size of 50–64 nm depending on the calcination time. The results of the Ca/P molar ratio from 1.839 to 1.847 prove that the nano-HAp powders are B-type biological hydroxyapatites, which has been confirmed by FTIR spectrum. In addition, the content of heavy metals such as As, Pb, Hg, Cd is detected within safety limits. These properties allow nano-HAp powders to be applied in food and medicine fields.